Ars :: Longa. - Chan, Paul (October)
A standard interpretation of the Latin phrase "Ars longa, vita brevis" is that it takes a long time to master an art or technology. Another interpretation is that art lasts, longer even than a human life. Paul Chan suggests a third possibility: that art extends life itself. To support this reading, he discusses the work of Chris Marker and the artist duo Arakawa and Gins, as well as describing experiences from his own private research in the domain of artificial intelligence. Hellenistic mathematicians Archimedes and Eratosthenes, who fused poetry with calculation to capture the "unbounded" or "infinite," are invoked through the work of the scholar Reviel Netz. Naturally, Faust appears.